Hierarchy of physical education goals as an expression of educational priorities among Polish teachers - Cezary Kuśnierz; Dariusz Pośpiech; Aleksandra Maria Rogowska (Universidade Federal de Santa Catarina, 2016)
The work of teachers has to be purposeful and well thought out in order to achieve desired results. Both theory and practice show that achieving success is combined with the adequate setting of educational goals and organizing them in a specific hierarchy. The objective of this study was the diagnosis of preferences concerning the hierarchy of physical education goals. A questionnaire developed by the European Physical Education Association was used as the research tool. Teachers perceived the goal of 'encouraging students to lead an active, healthy lifestyle' as the most important consideration. Its realization should result in lifelong physical activity and healthy lifestyle among students. From the results of this study it can be concluded that the following priorities of Polish teachers of physical education can be identified: health and physical fitness of pupils. Goals connected with shaping the social competences of pupils ranked lowest in importance